Purification of Single and Entangled Photons by Wavepacket Shaping. Issue 3 (20th January 2021) - Chuu, Chih‐Sung; Cheng, Chun‐Yuan; Wu, Chih‐Hsiang; Wei, Cheng‐Yeh; Huang, Sheng‐Yao; Chen, Yen‐Ju; Feng, Shih‐Wen; Yang, Chun‐Yao
Abstract: Single photons and entangled photons lie at the heart of photonic quantum technologies, whose optimal performances are normally reached when the purity of the single or entangled photons is high. However, the multiphoton emission, dissipation, and decoherence in practical realizations always lead to the degradation of the single‐ and entangled‐ photon quality. The purification of single or entangled photons is thus valuable to restore the quantum states and enhance the performance of quantum technologies. The applications of wavepacket shaping, an emerging quantum optics tool to manipulate the single‐ and entangled‐ photon wavefunctions, to purify single and entangled photons are reviewed. In particular, by modulating the single photons emitted from optically excited room‐temperature quantum dots, it is shown that the fast‐decaying multiphoton emission can be eliminated to obtain a low value of g (2) (0) that is independent of the excitation power. It is also shown that the two‐photon interference and polarization entanglement of the non‐degenerate biphotons from spontaneous parametric down‐conversion can be restored after modulating the biphotons with a periodic function. The works have potential applications in long‐distance quantum communication and linear optical quantum computation. Abstract : The purification of single and entangled photons is valuable to restore the quantum states and the optimal performance of quantum technologies. By modulating the wavepackets, high single‐photon purity independent of the excitation power is achieved in the colloidal quantum dots at room temperature. Two‐photon interference and polarization entanglement are also recovered in the spontaneous parametric downconversion.